The Influence of Behavioral Finance on Investment Decisions: A Systematic Literature Review - Anita, Siska Yuli (Penelitian dan Pengembangan Ilmu, 2024)
This research explores the impact of overconfidence on portfolio performance, with a focus on comparisons between retail and institutional investors through a systematic literature review approach. Overconfidence, as one of the main cognitive biases in behavioral finance, often influences investment decisions and portfolio results. This study identifies and analyzes how overconfidence affects retail and institutional investors differently, as well as its impact on portfolio management and investment policy. The findings show that retail investors, with limited knowledge and resources, tend to be more affected by overconfidence, which negatively impacts their portfolio performance. In contrast, institutional investors have access to better information and analytical tools, so they are better able to manage the impact of overconfidence. This research makes an important contribution to the behavioral finance literature by filling the knowledge gap regarding the differences in the impact of overconfidence between the two types of investors and offering practical insights for investment managers and market regulators. Limitations of the study and suggestions for future research are also discussed to expand understanding of this phenomenon.